Pengembangan Bakat Dan Minat Dengan Manajemen Peserta Didik - Muhammad Nur Hakim; Muhammad Nur Iskandar (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2023)
This research was carried out at the Public Senior High School 2 Mojokerto. The type of research used by researchers is qualitative descriptive research. The subjects of this study include the following: the principal, the student body, and the students. Researchers performed data clumping using observation methods, interviews, and documentation studies. The data analysis used is to use the triangulation method. Researchers aim to find out how the management of talent and interest development at The State High School 2 Mojokerto includes planning, implementing, and evaluating carried out in the development of talents and interests of students. The results of this study are the planning in the development of students’ talents and interests, namely by conducting joint deliberations to determine policies and meet the needs of students' needs. The implementation of the development of students’ talents and interests focuses on coaching and services provided to students. An evaluation is carried out to assess success in achieving goals in this case the development of talent and student interest.